Diminished ovarian reserve predisposes to premature luteinizing hormone surges in gonadotropin-releasing hormone antagonist cycles in In vitro fertilization - Puneet Kaur Kochhar; Pranay Ghosh (Wolters Kluwer Medknow Publications, 2020)
Context/Background: A premature luteinizing hormone (LH) surge, in in vitro fertilization (IVF) cycles with gonadotropin-releasing hormone (GnRH)-antagonist downregulation, leads to cycle cancellation. Currently, risk factors for the development of premature LH surge remain unknown. Objective: The aim of the study was to determine the incidence and identify the contributing factors for premature LH surge in IVF cycles with GnRH antagonist suppression. Design: This was a retrospective cohort study. Setting: IVF-embryo transfer program at a fertility and research center. Materials and Methods: The study included all patients undergoing IVF from December 1, 2014, to November 30, 2018, in whom GnRH-antagonist (cetrorelix 0.25 mg/d) flexible protocol was used. The primary outcome measure was the identification of premature LH surges (documented by a 2.5-fold increase in LH from the baseline above a threshold of 17 mIU/mL) with or without a decrease in E2and appearance of free fluid on ultrasound. Results: Premature LH surges occurred in 15 (2.16%) of 692 patients undergoing IVF with GnRH-antagonist suppression. Patients with premature surges had significantly lower ovarian reserve as compared to the controls (as seen from their higher age group, higher day 2 follicle-stimulating hormone (FSH), lower antral follicle counts, and lower anti-Müllerian hormone). Conclusions: Premature LH surge in a GnRH-antagonist cycle can lead to cycle cancellation and disappointment. Although this is a rare event, the incidence is higher in patients with diminished ovarian reserve. Further studies are needed to determine if giving the human chorionic gonadotropin trigger a day earlier or giving higher doses of GnRH-antagonist can benefit such cases.